2004
DOI: 10.1007/s10096-004-1151-3
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jiroveci isolates with dihydropteroate synthase mutations in patients with chronic bronchitis

Abstract: Since mutations in the dihydropteroate synthase (DHPS) gene possibly associated with sulfonamide resistance have been reported in patients with Pneumocystis jiroveci (previously carinii) pneumonia, and since P. jiroveci colonization has been recently demonstrated in patients with chronic pulmonary diseases, the present study aimed to investigate the possible occurrence of P. jiroveci DHPS mutations in patients with chronic bronchitis. P. jiroveci colonization was detected in 15 of 37 non-selected patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 35 publications
1
40
1
2
Order By: Relevance
“…In comparison with animal model experiments on transmission of Pneumocystis infection (5), the airborne transmission of P. jirovecii from the grandfather to the grandmother and the infant is the most probable explanation, especially in view of the high prevalence of P. jirovecii colonization of persons with chronic bronchial disease in our area and the grandfather's sputum production associated with this condition (15).…”
Section: Discussionmentioning
confidence: 90%
“…In comparison with animal model experiments on transmission of Pneumocystis infection (5), the airborne transmission of P. jirovecii from the grandfather to the grandmother and the infant is the most probable explanation, especially in view of the high prevalence of P. jirovecii colonization of persons with chronic bronchial disease in our area and the grandfather's sputum production associated with this condition (15).…”
Section: Discussionmentioning
confidence: 90%
“…It has been noted that patients with COPD and chronic bronchitis have an increased prevalence of colonization as well. Calderon et al have found that 41% to 100% of subjects with chronic bronchial disease have detectable colonization (28,30). Other groups have found that Pneumocystis is detectable in 37% of patients with severe COPD and only 5% of those with mild disease.…”
Section: Colonization In Animalsmentioning
confidence: 99%
“…In patients with COPD, for example, P. jirovecii DNA is present in approximately 20% of lung specimens obtained at the time of transplantation or lung resection, and the incidence of P. jirovecii colonization increases with worsening severity of COPD (35). P. jirovecii is also frequently found in the sputa of patients with pulmonary disease, and it has been identified in the sputa of approximately 50% of patients with chronic bronchitis (10).…”
mentioning
confidence: 99%